Acne Vulgaris Mimicking Cutaneous Lupus Erythematosus in an Adolescent: Report of a Rare Case - Irma Bernadette S. Sitohang; Agung Mohamad Rheza; Sondang P. Sirait; Eyleny Meisyah Fitri; Lis Surachmiati Suseno (Karger Publishers, 2021)
Acne vulgaris is a chronic and self-limiting disorder of the pilosebaceous unit which is primarily seen in adolescents. Acne vulgaris presents as polymorphic lesions, consisting of comedones, papules, pustules, cysts, nodules, scarring, and dyspigmentation. Acneiform presentation of cutaneous lupus erythematosus (CLE) is extremely rare. The presentation of CLE is notoriously diverse and often mimics a broad range of unrelated skin disorders. We present a case by referring to American College of Rheumatology (ACR) criteria for systemic lupus erythematosus (SLE); our patient's conditions did not meet any of the clinical criteria of the Systemic Lupus International Collaborating Clinics (SLICC) for SLE. Subsequent to thorough history-taking, physical examination, and laboratory evaluations, the diagnosis of acne vulgaris was established, and a diagnosis of CLE was excluded. As acneiform presentation of CLE is rare, we here present a case which resembled both acne vulgaris and CLE. We describe our experience in establishing the diagnosis of severe acne vulgaris accompanied by scars in a 12-year-old boy with a malar rash and scars on his frontal and malar area who had initially been misdiagnosed as having CLE. This unusual case highlights the broad spectrum of adolescent acne and the importance of clinical identification of the disease so that unnecessary workups might be avoided.